Various factors of attempted suicide in a selected area of Naogaon District - Halim, KS; Khondker, L; Wahab, MA; Nargis, F; Khan, SI (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):244-9. The abstract of this article is available on the PubMed website